Proteomics of Microparticles after Deep Venous Thrombosis - Ramacciotti, Eduardo (2010)
BACKGROUND: Microparticles (MP) are submicron size membrane vesicles released from activated cells that are associated with thrombosis and inflammation. MP present diverse biological expressions that may be linked to a unique subset of proteins derived from their origin cells. METHODS: To identify these proteins, plasma samples were taken from 9 patients with deep venous thrombosis (DVT) documented by duplex ultrasound, 9 with leg pain but negative for DVT by duplex, and 6 healthy controls without a history of thrombosis, for fold variation. MP were extracted from platelet-poor plasma, digested separately with trypsin and tagged using iTRAQ reagents. The digests were subjected to 2-D LC separation followed by MALDI tandem mass spectrometry. Peak lists were generated and searched against all human sequences. For protein identification, a minimum of two peptides at 95% confidence was required. Later, iTRAQ ratios were generated comparing relative protein levels of DVT patients to baseline. The proteomic analysis was performed twice for each blood sample. Proteins were considered elevated or depressed if the iTRAQ ratio (R) deviated by 20% change from normal and a p-value less than 0.05. RESULTS: Two proteins (Galectin-3 Binding Protein, [Gal3BP], R=1.76 and Alpha-2 macroglobulin [A2M] R=1.57) were differentially expressed on DVT patients. Nine proteins were depleted including fibrinogen beta and gamma chain precursors (R=0.65). CONCLUSIONS: These proteins influence thrombosis through inflammation, cell shedding, inhibition of fibrinolysis and hemostatic plug formation. Further studies are needed to confirm the mechanistic role of these proteins in the pathogenesis of venous thrombosis in humans.